Prevalence of Pseudomonas in dental unit water of private dental clinics and its antimicrobial susceptibility using MAR index - Karthik Shunmugavelu; T. Dhanaswathii; S.R. Janani (Amaltea Medical Publishing House, 2021)
The bacteriology of water in a dental unit is important as potentially pathogenic microorganisms like Pseudomonas may be present in dental water unit, which could be fatal for immuno-compromised patients and be of significant morbidity in immuno-competent patients. It is difficult to treat infections caused by Pseudomonas due to their resistance to many commonly used disinfectants and antibiotics. The aim of the present study was to evaluate the Pseudomonas contamination in dental unit water lines of a dental hospital outpatient department and to analyse the antimicrobial susceptibility of Pseudomonas.